774 Occupational exposure to combustion products and risk of developing rheumatoid arthritis. (24th April 2018) - Ilar, Anna; Wiebert, Pernilla; Saevarsdottir, Saedis; Askling, Johan; Gustavsson, Per; Alfredsson, Lars
Abstract : Introduction: Studies have suggested a potential association between traffic pollutants and rheumatoid arthritis (RA), but findings have been inconclusive. We therefore assessed the risk of RA from occupational exposure to combustion products in a large population-based case-control study. Methods: We included participants living in Sweden from 2006 to 2013. Incident cases of RA were enrolled from the Swedish Rheumatology Quality Register. Ten controls per case, matched on sex, age and county, were enrolled from the total population register. Work histories were available through population and housing censuses. We estimated exposure to asphalt fumes, diesel engine exhaust (DEE) and polycyclic aromatic hydrocarbons (PAH) from 1955 to 1995 with job-exposure matrices. Conditional logistic regression was used to estimate the risks of two histological subtypes of RA (seropositive or seronegative RA) from exposure to either of the combustion products taken separately or all of them combined. All estimates were adjusted for potential confounding from respirable crystalline silica dust and household disposable income. Results: We analysed 9180 cases and 81 367 controls. Ever exposure to DEE in men was associated with a marginally higher risk of seropositive RA (OR: 1.11, 95% CI: 1.00 to 1.23), which was slightly higher among workers with at least 20 years of exposure (OR: 1.22, 95% CI: 1.00 to 1.49). More than 20 years of asphalt fumes exposure was also associated with a higher risk estimate for seropositive RA among men (OR: 1.87, 95% CI: 1.05 to 3.31). Being exposed to asphalt fumes, DEE or PAH combined for more than 20 years resulted in an OR of 1.22 (95% CI: 1.03 to 1.45) among men and 1.27 (95% CI: 0.50 to 3.26) among women for seropositive RA. Discussion: Long-term exposure to combustion products may increase the risk of seropositive RA among men after adjustments for respirable crystalline silica dust and household disposable income.